SVALKA: A Long Noncoding Cis-Natural Antisense RNA That Plays a Role in the Regulation of the Cold Response of Arabidopsis thaliana - Nicholas M. Kiger; Susan J. Schroeder (Non-Coding RNA, 2024)
RNA plays important roles in the regulation of gene expression in response to environmental stimuli. SVALKA, a long noncoding cis-natural antisense RNA, is a key component of regulating the response to cold temperature in Arabidopsis thaliana. There are three mechanisms through which SVALKA fine tunes the transcriptional response to cold temperatures. SVALKA regulates the expression of the CBF1 (C-Repeat Dehydration Binding Factor 1) transcription factor through a collisional transcription mechanism and a dsRNA and DICER mediated mechanism. SVALKA also interacts with Polycomb Repressor Complex 2 to regulate the histone methylation of CBF3. Both CBF1 and CBF3 are key components of the COLD REGULATED (COR) regulon that direct the plant’s response to cold temperature over time, as well as plant drought adaptation, pathogen responses, and growth regulation. The different isoforms of SVALKA and its potential to form dynamic RNA conformations are important features in regulating a complex gene network in concert with several other noncoding RNA. This review will summarize the three mechanisms through which SVALKA participates in gene regulation, describe the ways that dynamic RNA structures support the function of regulatory noncoding RNA, and explore the potential for improving agricultural genetic engineering with a better understanding of the roles of noncoding RNA.